2023
DOI: 10.3389/fonc.2023.1126482
|View full text |Cite
|
Sign up to set email alerts
|

JNJ-64619178 radiosensitizes and suppresses fractionated ionizing radiation-induced neuroendocrine differentiation (NED) in prostate cancer

Abstract: BackgroundRadiation therapy (RT) is a standard treatment regimen for locally advanced prostate cancer; however, its failure results in tumor recurrence, metastasis, and cancer-related death. The recurrence of cancer after radiotherapy is one of the major challenges in prostate cancer treatment. Despite overall cure rate of 93.3% initially, prostate cancer relapse in 20-30% patients after radiation therapy. Cancer cells acquire radioresistance upon fractionated ionizing radiation (FIR) treatment, eventually und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Accordingly, inhibiting FOXD1 could potentially reduce breast cancer metastasis by inactivating the enhancers associated with EMT. Furthermore, recent studies have shown that molecular targeting therapies can increase the sensitivity of established treatments, such as chemotherapy and radiotherapy, in various types of cancer ( 39 41 ). One of the primary challenges in developing FOXD1-targeting therapies is the lack of available FOXD1 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, inhibiting FOXD1 could potentially reduce breast cancer metastasis by inactivating the enhancers associated with EMT. Furthermore, recent studies have shown that molecular targeting therapies can increase the sensitivity of established treatments, such as chemotherapy and radiotherapy, in various types of cancer ( 39 41 ). One of the primary challenges in developing FOXD1-targeting therapies is the lack of available FOXD1 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…PRMT5 inhibition can also improve ICB outcomes through the augmentation of cGAS-STING responses and PD-L1 expression [ 276 , 277 ]. Two recent reports have demonstrated that PRMT5 inhibition impairs DNA repair, enhances radiosensitivity in multiple CRPC cell lines, and prevents RT-induced neuroendocrine differentiation and tumor growth in CRPC-AR tumor models [ 278 , 279 ]. PRMT5 has also been identified as a suppressor of gemcitabine toxicity in whole-genome CRISPR screens of pancreatic cells [ 280 ].…”
Section: Emerging Targets In Crpcmentioning
confidence: 99%